Anti-oxidative enzymes in relation to iron toxicity caused by differential soil ironcontent in winter rice (Oryza sativa) of Assam, India - MADHUSMITA BARUAH; PRIYANKA DAS; NILAY BORA; SUNAYANA RATHI; BORSHA NEOG (The Indian Journal of Agricultural Sciences)
A study was conducted at Assam Agricultural University, Jorhat, Assam to know the effect of differential soil iron content on plant (leaves and grain) iron content together with the activities of some anti-oxidative enzymes, viz. peroxidase (POD), superoxide dismutase (SOD) and catalase (CAT) in a few popular rice varieties of Assam. The result of the pot experiment under rain protected condition revealed that application of iron fertilizer to soil (1 L of 50 ppm FeSO4.7H2O to 6 kg soil) of initial soil iron content 159.40 mg/kg before planting led to increase in leaf iron content from 39.16 mg/100 g (control) to 45.36 mg/100 g (treated) at harvesting stage. However, no iron toxicity symptoms were observed which might be due to higher activities of CAT at maximum tillering stage and SOD at grain filling stage. The study revealed that the rice varieties Ranjit, Mahsuri and Kajoli chakua may respond to application of iron fertilization without producing iron toxicity symptom and yield more than 100% iron content in brown rice than that of control.